2013
DOI: 10.3109/00016489.2013.797604
|View full text |Cite
|
Sign up to set email alerts
|

Surgical complications following cochlear implantation in adults based on a proposed reporting consensus

Abstract: Conclusion: The rate of severe complications was low and cochlear implantation is a relatively safe procedure. Standardization is crucial when reporting on cochlear implant complications to ensure comparability between studies. A consensus on the reporting of complications proposed by a Danish team of researchers was applied, evaluated and found beneficial.Objectives:To report the surgical complications following cochlear implantation at our centre, applying and evaluating a proposed reporting consensus.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 19 publications
1
31
0
Order By: Relevance
“…However, an increase of existing tinnitus, varying from 2% to 9% of patients, as well as a new onset of tinnitus, is described. The induction of tinnitus occurs in 1% to 5% of patients according to recent studies describing the complications following cochlear implantation …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, an increase of existing tinnitus, varying from 2% to 9% of patients, as well as a new onset of tinnitus, is described. The induction of tinnitus occurs in 1% to 5% of patients according to recent studies describing the complications following cochlear implantation …”
Section: Introductionmentioning
confidence: 99%
“…The induction of tinnitus occurs in 1% to 5% of patients according to recent studies describing the complications following cochlear implantation. 3,4 Most studies that report on the effect of cochlear implantation on tinnitus have been published in the last decade. However, a current systematic review of the literature following evidenced-based medicine (EBM) principles is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…In 10 studies, no clear report was available regarding CTN preservation or iatrogenic lesion. Outcome of these studies did not evaluate CTN status . Seven studies were excluded due to a lack of preoperative diagnosis for ear surgery because it was unclear if patients with inflammatory disease were included.…”
Section: Resultsmentioning
confidence: 99%
“…Outcome of these studies did not evaluate CTN status. 20,21,23,[28][29][30]32,33,36,37 Seven studies were excluded due to a lack of preoperative diagnosis for ear surgery because it was unclear if patients with inflammatory disease were included. In addition, studies with a low number (< 5) of reported patients were excluded.…”
Section: Data Analysesmentioning
confidence: 99%
“…The most common complications are infection (wound infection and meningitis), facial nerve trauma, electrode migration/misplacement, vertigo, and tinnitus [1,2] . Pneumocele following cochlear implantation is very rare [3][4][5][6][7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%